2021
DOI: 10.1039/d1tb01344k
|View full text |Cite
|
Sign up to set email alerts
|

LSPR immuno-sensing based on iso-Y nanopillars for highly sensitive and specific imidacloprid detection

Abstract: A label-free sensitive and specific LSPR immunosensor for imidacloprid detection based on a 2D nanostructured metasurface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…As previously described, 18 the spectral shifts of the LSPR peaks were measured using an experimental setup consisting of a halogen lamp that provides unpolarized white light to the nanostructured pattern by the use of a 10X (N.A. 0.25) objective (a circular light spot of about 400 μm).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously described, 18 the spectral shifts of the LSPR peaks were measured using an experimental setup consisting of a halogen lamp that provides unpolarized white light to the nanostructured pattern by the use of a 10X (N.A. 0.25) objective (a circular light spot of about 400 μm).…”
Section: Methodsmentioning
confidence: 99%
“…The plasmonic properties of nanoscale systems and their sensing performance are jointly determined by physicochemical factors such as dielectric properties and the material composition as much as geometric factors. For this reason, the shape, size, period, and symmetry of the engineered plasmonic nanostructure are designed to obtain enhanced field distribution at the desired wavelength or even the effective sensing volume available for a particular analyte. Over the years, our team had also empirically observed that some patterns of specific pitches provide superior performance for a particular analyte, and so we have developed LSPR- and SERS-based sensors of molecules, biomacromolecules, and viruses, e.g., Thiram pesticide on Thue-Morse arranged triangular nanopillars, bovine serum albumin and imidacloprid insecticide on iso-Y-shaped nanopillars, , rotavirus on Achiral Octupolar arranged triangular nanopillars, and hepatitis A on pyramidal nanoholes . In this study, we explore the functionality and limitations of AAL on a 2D plasmonic photonic crystal–glass/ITO substrate with gold triangular pillars arranged in Achiral Octupolar pattern with a pitch of 25, 50, 100, and 263 nm (AchOct 25/50/100/263).…”
Section: Introductionmentioning
confidence: 99%
“…The array was fabricated by EBL lithography, its optical response was numerically evaluated, and a sensitivity of 412 nm/RIU was measured. The proposed platform was functionalized with IgG and allowed for the detection of a pesticide (namely, the imidacloprid) in the dynamic range of 1-1000 ng/mL achieving an LOD of 1 ng/mL [106]. Chen et al proposed instead a multiplexed detection based on IgGs using large-scale plasmonic nanoarrays based on thermal dewetting of gold films of 10 nm thickness.…”
Section: Lspr-based Plasmonic Nanoarraysmentioning
confidence: 99%
“…The protein layers can be identified from observing the difference in the diffraction pattern of the array before and after functionalization with the protein layer, which is a label-free technique that provides miniaturization and easier integration. With appropriate functionalization, gold nanoparticles can even provide high specificity to particular analytes [ 97 ].…”
Section: Plasmonic Materialsmentioning
confidence: 99%
“… Versatility of gold nanoparticles; (from left to right) nanospheres [ 60 ], nanostars [ 88 ], nanorods [ 89 ], nanocages [ 92 ], nanodiscs [ 90 ], nanoholes [ 93 ], and iso-Y [ 97 ], to support plasmonic resonance all over the visible range. Nanostars and nanodiscs can support multiple resonances.…”
Section: Figurementioning
confidence: 99%